Analisis Peran Guru dalam Pembentukan Pendidikan Karakter Siswa Kelas IV Sekolah Dasar - Arifin, Arifin; Nurhasanah, Enung; Jamaah, Jamaah (Jurnal Evaluasi dan Kajian Strategis Pendidikan Dasar, 2024)
This research focuses on analyzing the role of teachers in forming the character of class IV students at SDN 17 Woja. The aim of this research is to analyze the role of teachers as educators, demonstrators, class managers, motivators and evaluators in the formation of student character, as well as to identify supporting and inhibiting factors in this process. The character values ​​that are the focus of the research include religious, honest, disciplined, independent, socially caring and responsible. This research uses a qualitative method with a descriptive approach. The data collection techniques used were observation, interviews and documentation involving fourth grade teachers and students as research subjects. Data analysis stages include data collection, data reduction, data presentation, and drawing conclusions. The validity of the data was tested using triangulation techniques. The results of the research show that the role of teachers in forming the character of class IV students at SDN 17 Woja includes several important aspects: (1) Teachers as educators, demonstrators, class managers, motivators and evaluators play a significant role in shaping student character, (2) Supporting factors identified were a conducive family environment and the availability of adequate facilities and infrastructure, while inhibiting factors included a lack of support from the family and several obstacles originating from the teachers themselves.